Brachial Plexus Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The neonatal and follow-up records of 52 children with neonatal acquired brachial plexus palsy (BPP), born in 1981-89 in a mixed urban-rural county of Skaraborg, Sweden, were analyzed retrospectively at 4-14 years after birth and motor handicaps were evaluated at the Department of Child Habilitation, Central Hospital, Skovde, Sweden.